2010
DOI: 10.1111/j.1600-9657.2010.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance and reinforcement of immature roots with gutta percha, mineral trioxide aggregate and calcium phosphate bone cement: a standardized in vitro model

Abstract: Endodontic treatment of immature teeth is often complicated because of flaring root canals and open apices for which apexification is needed. Long-term prognosis for these teeth is surprisingly low because of cervical root fractures occurring after an impact of weak forces. In this study, an experimental model was developed to determine the fracture resistance of immature teeth and to test the hypothesis that endodontic materials succeed in reinforcing them. Compact and hollow bone cylinders from bovine femurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 38 publications
4
47
0
4
Order By: Relevance
“…According to Andreasen et al 31) and Cauwels et al 32) , MTA increased the fracture resistance of immature teeth. In the present study, MTA-based root canal sealer MTA Fillapex showed signifi cantly higher fracture resistance than the negative control group and was not signifi cantly different from AH Plus and iRoot SP.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Andreasen et al 31) and Cauwels et al 32) , MTA increased the fracture resistance of immature teeth. In the present study, MTA-based root canal sealer MTA Fillapex showed signifi cantly higher fracture resistance than the negative control group and was not signifi cantly different from AH Plus and iRoot SP.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 96%
“…Its MTA-based composition contains salicylate resin, diluting resin, natural resin, nanoparticulated silica, and bismuth trioxide. In several studies, it was shown that MTA as a root canal fi lling material strengthened the root against fracture 31,32) . This could be related to the phenomenon of delayed strength development of MTA, which occurs after 24 h of setting 33) .…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 99%
“…In other studies, MTA as a root canal filling material strengthened the root against fracture. 20,21 In the current study, the MTA-based root canal sealer MTA Fillapex showed significantly higher fracture resistance compared with the negative control group, although it was not significantly different from the other root canal sealers tested. This may be due to the presence of resins in MTA Fillapex.…”
mentioning
confidence: 50%
“…12 The cementation may be performed with resin composite, 13 glass ionomer cement 16 and resin cements 17 aiming to a greater adhesion between post and dentine wall of root canal. 18 Glass fiber posts are an alternative for the restoration of teeth with IR due they have modulus of elasticity similar to dentine. 19,20 The use of an apical plug with MTA has been suggested for endodontic therapy of teeth with IR, [21][22][23] resulting in a faster treatment and inducing the mineralized tissue formation in the root apex.…”
Section: 10mentioning
confidence: 99%